DIPG-75. PRECISION MEDICINE FOR PAEDIATRIC HIGH-GRADE DIFFUSE MIDLINE GLIOMAS - RESULTS FROM THE ZERO CHILDHOOD CANCER COMPREHENSIVE PRECISION MEDICINE PROGRAM. (4th December 2020) - Khuong-Quang, Dong-Anh; Nagabushan, Sumanth; Manoharan, Neevika; Arndt, Greg; Barahona, Paulette; Cowley, Mark J; Ekert, Paul G; Failes, Tim; Bolanos, Noemi Fuentes; Gauthier, Maely; Gifford, Andrew J; Haber, Michelle; et al.
Abstract: The Australian Zero Childhood Cancer (ZERO) program aims to assess the feasibility of a comprehensive precision medicine approach to improve outcomes for patients with an expected survival <30%. ZERO combines molecular profiling (whole genome sequencing, whole transcriptome sequencing, DNA methylation profiling) with in vitro high-throughput drug screening (HTS) and patient-derived xenograft drug efficacy testing. We report on the cohort of patients with midline high-grade glioma (HGG), including H3-K27M DMG, enrolled on the pilot study (TARGET) and on the ongoing ZERO clinical trial (PRISM). We identified 48 patients with midline HGG. Fresh or cryopreserved samples were submitted in 37 cases and cell culture was attempted in 30/37 cases with 45% success rate. The most commonly mutated genes/pathways identified by molecular profiling include H3-K27M mutations, DNA repair pathway, and PI3K/mTOR pathway. Two targetable fusions (NTRK and FGFR1) were reported. Five patients with germline alterations were identified. Thirty-five (72%) patients received a therapeutic recommendation from the ZERO molecular tumour board and the main recommended therapies were mTOR inhibitors, PARP inhibitors or tyrosine kinase inhibitors. HTS added evidence for the recommended therapy (n=3) or identified novel potential therapy (n=1). Out of the 35 patients, 16 received a recommended drug. Response to treatment was complete response for five months (n=1), partial response for nine months (n=1), stable disease (n=4), and progressive disease (n=10). These results highlight the feasibility of the ZERO platform and the value of fresh biopsy, necessary for pre-clinical drug testing. Targetable alterations were identified leading to clinical benefit in six patients.